Tafsir Nur al-Ihsan Karangan Haji Muhammad Sa'id bin Umar: Satu Kupasan - Ibrahim, N. (Universiti Sains Islam Malaysia, 2024)
Tafsir Nur al-Ihsan in Jawi script was written in 1927 by Haji Muhammad Sa'id bin Umar, a well-known Malay scholar from Kedah, Malaysia. This article explores the author's expertise in development of Quranic interpretation writing in Malay-Archipelago and writing methodology that had been used by the author in Kitab Tafsir Nur al-Ihsan. Information about it was gathered using qualitative method. Research result shows this kitab was that most comprehensive 30 juzu' Quranic Interpretation. The author had used tafsir ijmali method and based on mushaf structure that contained an explanation about asbabun nuzul, ayat ahkam, hurf muqatta'ah and Israiliyyat stories. The interpretations presented in this kitab is simple, moderate and yet very much suitable and relevant that is being used until today in Qurnic Interpretation studies in mosques in Malaysia, mainly in the northen of Peninsular Malaysia.